Analysis of thermoelastic laminated Timoshenko beam with time-varying delay - Besma Founas; Fares Yazid; Fatima Siham Djeradi; Djamel Ouchenane; Erhan Pişkin; Salah Boulaaras (Partial Differential Equations in Applied Mathematics, 2024)
This document presents a study into a linear thermoelastic laminated Timoshenko beam featuring a time-varying delay. Utilizing the semigroup method and the variable norm technique, we establish the well-posedness of the system. Subsequently, leveraging the energy method under appropriate conditions, we demonstrate the system’s exponential stability.